Nursing home staff mental health during the COVID-19 pandemic in the Republic of Ireland - Brady, Conan Laurence (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2023)
This thesis comprises three main studies. The aim of this project was to characterise nursing home staff mental health during the COVID-19 pandemic in the Republic of Ireland. Study 1: Cross-sectional survey of nursing home staff working in the Republic of Ireland during the third wave of the COVID-19 pandemic (November 2020-January 2021) The objective was to conduct a national, cross-sectional survey of nursing home staff in the Republic of Ireland during the third wave of the COVID-19 pandemic. I hypothesised that there may be significant differences in these outcomes between jobs or professions. 390 responses were collected. Moderate-severe post-traumatic stress disorder (PTSD) symptoms were found in 45.1% (95% CI 40.2-50.1%) of all staff. A World Health Organisation-5 (WHO-5) wellbeing index score ?32, indicating low mood, was reported by 38.7% (33.9-43.5%) of staff; significantly more nurses reported low mood. Suicidal ideation and suicide planning were reported respectively by 13.8% (10.4-17.3%) and 9.2% (6.4-12.1%) of participants with no differences between groups. HCAs reported significantly higher moral injury than nonclinical staff. Nurses were more likely to use approach coping styles than nonclinical staff. Study 2: Cross-sectional, anonymous online survey one year after the original study of nursing home staff mental health in the Republic of Ireland (November 2021-January 2022) The objective was to conduct a follow-up, anonymous online survey one year after the original study to further characterise nursing home staff mental health and to assess if there have been changes in these outcomes over time. I hypothesised the rollout of vaccination, and the easing of pandemic-related restrictions would improve mental health outcomes. 229 responses were collected. More staff reported moderate-severe post-traumatic stress symptoms (Survey 1 (S1) 45%; S2 65%; p<0.01), depression (S1: 39%; S2 57%; p<0.01), suicidal ideation (S1: 14%; S2 18%; p<0.01) and suicidal planning (S1: 9%; S2 15%; p=0.04) later in the pandemic. There was a higher degree of moral injury in Survey 2 (S2) (S1: 20.8 standard deviation (SD) 9.1; S2: 25.7 SD (11.3), p<0.01) and use of avoidant (maladaptive) coping styles at S2 (S1: 20.8 (6.3); S2 23.0 (6.3); p<0.01) with no significant differences found in the use of approach (adaptive) coping styles. Staff reported significantly more concerns at S2 regarding contracting Covid-19 (p<0.01), social stigma (p=0.01), job stress (p<0.01), doubts about personal protective equipment (p<0.01) and systems and processes (p<0.01). This study shows that mental health outcomes have significantly worsened over time in this cohort. My hypothesis has not been supported. Study 3: Multiple linear regression analyses of correlates of depression, post-traumatic stress, and moral injury in nursing home staff in the Republic of Ireland during the COVID-19 pandemic. The objective was to perform analyses of the data collected in both surveys to ascertain if demographic and employment characteristics, COVID-19 exposure, perceptions regarding the pandemic, and coping styles correlate with depressive symptoms, post-traumatic stress symptoms and moral injury. Based upon previous related research, I hypothesised that significant correlates of these measures would exist. Maladaptive coping was found to moderately correlate with worse outcomes in every measure in both Survey 1 and Survey 2. This may provide a target for mitigating poor outcomes in this cohort in future.
APPROVED
Keywords: nursing homes; COVID-19; mental health; post-traumatic stress disorder; moral injury; depression; suicidal ideation